Fresh water the precious resource - Davies, Delwyn G., 1908- 4 0 16; 5 American Museum of Natural History (Garden City, N.Y : Published for the American Museum of Natural History [New York] by the Natural History Press, 1969)
Discusses the physical and chemical properties of water, its biological importance to all forms of life, man's extensive uses but limited sources of fresh water, and the modern problems of water supply, pollution, and purification.
Keywords: 2 -- 0; 6; Juvenile literature. -- Water-supply;Water.;Water supply. -- 20; 20; 2